2015
DOI: 10.1007/s11999-015-4218-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Granulocyte-colony Stimulating Factor on Rotator Cuff Healing After Injury and Repair

Abstract: Background The failure rate of tendon-bone healing after repair of rotator cuff tears remains high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…The average weight of the animals was 170–230 g. The animals were housed in wire mesh cages at room temperature with 12:12-h light-dark cycles and were maintained on standard rat chow and tap water. Animals were randomly divided into seven groups (12 animals each): group 1: a negative control; group 2: induced endometrial fibrosis (pathological control); group 3: induced endometrial fibrosis that received human mesenchymal stem cells (hMSCs) (2 × 10 6 cells/ml intraperitoneally/week) [ 8 ]; group 4: induced endometrial fibrosis that received 0.1 mg/kg daily oral estrogen [ 8 ], group 5: induced endometrial fibrosis that received 2 × 10 6 hMSCs + 0.1 mg/kg and daily oral estrogen; group 6: induced endometrial fibrosis that received neupogen (300 µg/ml IV injection in tail vein, three times/week) [ 9 ], and group 7: induced endometrial fibrosis that received 2 × 10 6 hMSCs + 300 µg/ml neupogen.…”
Section: Methodsmentioning
confidence: 99%
“…The average weight of the animals was 170–230 g. The animals were housed in wire mesh cages at room temperature with 12:12-h light-dark cycles and were maintained on standard rat chow and tap water. Animals were randomly divided into seven groups (12 animals each): group 1: a negative control; group 2: induced endometrial fibrosis (pathological control); group 3: induced endometrial fibrosis that received human mesenchymal stem cells (hMSCs) (2 × 10 6 cells/ml intraperitoneally/week) [ 8 ]; group 4: induced endometrial fibrosis that received 0.1 mg/kg daily oral estrogen [ 8 ], group 5: induced endometrial fibrosis that received 2 × 10 6 hMSCs + 0.1 mg/kg and daily oral estrogen; group 6: induced endometrial fibrosis that received neupogen (300 µg/ml IV injection in tail vein, three times/week) [ 9 ], and group 7: induced endometrial fibrosis that received 2 × 10 6 hMSCs + 300 µg/ml neupogen.…”
Section: Methodsmentioning
confidence: 99%
“…After acute traumatic brain injury, G-CSF application reduced bacteremia, although overall survival was not improved [ 149 ]. However, contradictory effects were reported concerning local healing: In a rodent model of full-thickness supraspinatus tendon defects, G-CSF treatment locally increased cellularity after rotator cuff repair, but failed to improve structural healing [ 150 ]. By contrast, accelerated wound healing was found after topical G-CSF application [ 151 ].…”
Section: Neutrophils As a Therapeutic Target In Traumamentioning
confidence: 99%
“…Mesenchymal stem cell transplantation [11][12][13][14] and administration of biological growth factors, such as recombinant human bone morphogenetic protein-2 (rhBMP-2) [6,14,15], transforming growth factor (TGF) -beta1 [16], fibroblast growth factor (FGF) [5] and granulocyte colony stimulating factor (G-CSF) [17], have been performed in recent studies. Though most studies using growth factors failed to form fibrocartilage tissue at the tendon-bone interface, Hashimoto et al reported that they succeeded in generating a tendon-bone junction similar to normal enthesis using rhBMP-2 in a rabbit model [15].…”
Section: Introductionmentioning
confidence: 99%